Demand for TV broadcasts of UEFA Champions League games in Danish television - The impact of uncertainty of outcome, stardom, and local heroes - Oliver Budzinski; Arne Feddersen; Philipp Kunz-Kaltenhäuser (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2022)
There are noticeable conceptual differences between competing concepts for organizing the highest level of European Football. One major conceptual controversy is concerned with the question whether fans have a stronger preference for (more) games between the top teams over a broad participation of less well-known clubs representing more of the regions in Europe or vice versa. Since sports economics theory offers explanations for both views, this paper takes an empirical approach and analyzes revealed fan preferences in a market outside of the Big-5 leagues. It examines the impact of uncertainty of outcome, market value as well as local heroes (domestic players & teams) as determinants of demand in national TV in Denmark. It uses representative panel data of national TV demand for UEFA Champions League games in Denmark from 2006/07-2018/19. We estimate a semi-logarithmic OLS regression model with team fixed-effects where the dependent variable is the natural logarithm of the average TV audience of UCL matches broadcasted in Denmark. We find that the presence of superstar clubs as measured by accumulated market value of players increases broadcast audience significantly, whereas the number of superstar players in a game did not. Matches including Danish clubs (domestic clubs) as well as the number of Danish players on a team's roster (local hero players) show no robust effect on TV audience. Uncertainty of outcome increases TV demand in our model, supporting the UOH for TV audiences and furthering the discussion around diverging preferences between stadium attendance and TV demand. – – There are noticeable conceptual differences between competing concepts for organ-izing the highest level of European Football, One major conceptual controversy is concerned with the question whether fans have a stronger preference for (more) games between the top teams over a broad participation of less well-known clubs representing more of the regions in Europe or vice versa, Since sports economics theory offers explanations for both views, this paper takes an empirical approach and analyzes revealed fan preferences in a market outside of the Big-5 leagues, It examines the impact of uncertainty of outcome, market value as well as local heroes (domestic players & teams) as determinants of demand in national TV in Denmark, It uses representative panel data of national TV demand for UEFA Champions League games in Denmark from 2006/07-2018/19, We estimate a semi-logarithmic OLS regression model with team fixed-effects where the dependent variable is the natural logarithm of the average TV audience of UCL matches broadcasted in Denmark, We find that the presence of superstar clubs as measured by accumulated market value of players increases broadcast audience significantly, whereas the number of superstar players in a game did not, Matches including Danish clubs (domestic clubs) as well as the number of Danish players on a team's roster (local hero players) show no robust effect on TV audience, Uncertainty of outcome increases TV demand in our model, supporting the UOH for TV audiences and furthering the discussion around diverging preferences between stadium attendance and TV demand.
Keywords: Z20; L83; D47; 330; sport broadcasting demand; UEFA Champions League; European Super League; uncertainty of outcome; league management; superstars; local heroes; European football; soccer